ROLE-PLAYING GAME (RPG) APPLICATION TO FOSTER ENGLISH VOCABULARY AND GRAMMAR FOR EFL STUDENTS - Subandowo, Dedy (Jurnal Pedagogy, 2016)
This research focuses on Role-Playing Game application as an English learning media of vocabulary and grammar for EFL students. RPG application provides vocabulary and grammar learning materials in interesting way to create a new learning atmosphere where the students do not get easily bored when learning those aspects. The steps of this developmental research (RnD) are analyzing, designing, developing, and evaluating. The research subjects are the students of Universitas Muhammadiyah Metro. The instrument of this research is questionnaire. The questionnaire in this research is used to collect data which is divided into two aspects, readability and implementability. The data are analyzed using Percentage Analysis Data. The result shows that the product is developed well. The readability aspect, the result of one-to-one is 72%, then in small group is increased to 80% and in the field test it is 87%. The implementability aspect, the result of one-to-one is 71%, in small group is 81% and in field test is 87%. Thus, the product is developed well after each phase of the research. Based on the result of the research, it can be concluded that Materials in RPG application can be learned attractively and interestingly.